Penguatan Literasi dan Karakter Anak Migran Indonesia melalui Program Volunteering Internasional di Malaysia - Safril; Muslihatun Maulidian; Bustami Adianto; Emma Susandra Dewi; Jauharul Mawahib; Miftah Addini; Grozny Nur Huda; M Faiz Chishomuddin; Jelita Manullang (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This community service article aims to describe and analyze the implementation of an international volunteering program in strengthening literacy and character development among Indonesian migrant children in Malaysia. The activity was conducted through the International Volunteer and Youth Fellowship (IVYF) Malaysia–Singapore 2026 program at Sanggar Belajar Hulu Langat and Beranang as non-formal education centers for migrant children. The program involved 60 migrant children from elementary to senior high school levels who participated in various educational and character-building activities. This community service employed a qualitative descriptive approach through participatory observation, documentation, and volunteer reflection during the implementation process. The activities included learning assistance, basic literacy strengthening in reading and writing, character education, and interactive learning through educational games and cultural exchange activities. The results showed that the program contributed positively to improving children’s learning participation, literacy engagement, self-confidence, cooperation, and social interaction. The learning through play approach created a more engaging, interactive, and meaningful learning environment for children with diverse educational backgrounds. In addition, the program also enhanced social awareness and cross-cultural understanding among volunteers involved in the activities. This community service demonstrates that international volunteering can serve as an effective community-based approach in supporting inclusive education and sustainable development goals, particularly in providing quality education opportunities for vulnerable groups such as migrant children